Navigating Tradition and Innovation: A Comprehensive Study of Organizational Development in East Java's Islamic Boarding Schools - Darojat, Shofiyatun (Abjadia : International Journal of Education, 2023)
This research explores the transformative journey of Islamic boarding schools in Indonesia, the oldest Islamic educational institutions, emphasizing their crucial role in intellectual, spiritual, and character development. The study underscores the need for a comprehensive transformation of Kyai (Islamic leaders) to modernize educational institutions while preserving traditional Islamic teachings. The research classifies Islamic boarding schools into three types: traditional, modern, and a combination. Each type follows a distinct organizational development model. Traditional schools focus on defending heritage values, intervening when necessary, taking natural actions, and incorporating uncontroversial changes. Modern schools adopt a process involving diagnosis, revitalization, envisioning, identification, and stabilization. Combined model schools integrate heritage preservation, diagnosis, intervention, balance, and stabilization. The methodology employs a qualitative approach with a case study design, utilizing interviews and triangulation for data validation. The findings highlight the leadership roles specific to each type. Traditional schools maintain a natural progression rooted in tradition, while modern schools and combined model schools follow distinct stages in organizational development to adapt to changing educational landscapes. This research contributes valuable insights to the ongoing dialogue on harmonizing traditional Islamic values with modern educational needs in the context of Islamic boarding schools in Indonesia